Implementation of Corporate Social Responsibility (CSR) PT. Sari Lembah Subur to the Community of Genduang Village - Achmad Amiruddin; Didi Rukmana; Sainul Aulia Anugra (Universitas Muhammadiyah Malang, 2022)
CSR (Corporate Social Responsibility) is one of the obligations that must be carried out under the contents of article 74 of the new Law of Limited Liability Company (UUPT) of 2007. PT. Sari Lembah Subur is an extensive farm area of ​​about 450 ha. Besides managing its own plantation, it also processes palm oil products from smallholder plantations around the company. The company purchases palm fresh fruit bunch (FFB) from smallholder plantations/farmers as one of its CSR programs. In addition, several CSR programs carried out by the company are related to social and environmental matters so that the image of PT. Sari Lembah Subur remains good from the perspective of the community living around the company. Based on the description above, the researchers are interested in researching the